PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS LINKTREE DENGAN MODEL INQUIRY BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA SDN MANGKUKUSUMAN 1 TEGAL - Fidianingrum Yuniasih; Taufiqulloh; Yoga Prihatin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Observation data carried out at SD Negeri Mangkukusuman 1, found that the use of learning media has not been developed innovatively and does not support various types of intelligence from students, so that it does not attract students' interest in learning and results in low students' critical thinking skills in the content of science lessons. This research aims to develop Linktree-based science lesson content learning media with an Inquiry Based Learning model that meets feasible and effective criteria in improving students' critical thinking skills. This research uses a research and development (R&D) model that adopts the EDED development model which includes the exploration, development, evaluation and dissemination stages. Data collection uses interview, observation, questionnaire, test and documentation instruments. This study involved 56 students divided into 2 groups, namely the control group which amounted to 28 students of SDN Mangkukusuman 1 class VI A and the experimental group of 28 students of SDN Mangkukusuman 1 class VI B. The results of the study showed that Linktree-based learning media was considered very feasible by validators with an average of 91.6% in the media aspect, 94.4% in the material aspect. Linktree-based learning media is also effective in improving students' critical thinking skills with an average difference of pretest and posttest scores of 28, as well as the acquisition of N-gain in the experimental group trial of 0.498 and is included in the moderate criteria. The resulting conclusion is that the development of Linktree-based learning media with the Inquiry Based Learning model can meet the learning needs of students and overcome the problem of low critical thinking skills of students. Linktree-based learning media with the Inquiry Based Learning model is suitable for use in learning and is effective in improving students' critical thinking skills.